High-Throughput Analysis Reveals Seasonal Variation of the Gut Microbiota Composition Within Forest Musk Deer (Moschus berezovskii) - Hu, Xiaolong; Liu, Gang; Li, Yimeng; Wei, Yuting; Lin, Shaobi; Liu, Shuqiang; Zheng, Yunlin; Hu, Defu (Frontiers in Microbiology, 2018)
The gut microbiota plays a key role in the nutritional ecology of ruminants, and host diet has a significant effect on these microbial communities. Longitudinal studies assessing variation of seasonal microbiota in animals can provide a comparative context for interpreting the adaptive significance of such changes. However, few studies have investigated the effects of seasonally-related dietary shifts on the gut microbial communities of endangered forest musk deer (FMD), and the national breeding programs need this information to promote the growth of captive populations. The present study applied bacterial 16S rRNA genes based on high-throughput sequencing to profile the fecal microbial communities of FMD across four seasons. Microbial diversity was higher in seasons with dry leaf diets (winter and spring) compared to seasons with fresh leaf diets (summer and autumn). The dominant microbial phyla were Firmicutes and Bacteroidetes, and the core bacterial taxa also comprised mostly (94.40% of shared OTUs) Firmicutes (37 taxa) and Bacteroidetes (6 taxa), which were relatively stable across different seasons. The Firmicutes-Bacteroidetes ratio declined in seasons with fresh leaf diets relative to seasons with dry leaf diets, and the dominant genera among the four seasons showed no significant variation in abundance. This work explores the seasonal variation in the microbial communities of FMD for the first time, and reveals how gut microbial community dynamics vary seasonally in accordance with differences in dietary plants (fresh and dry leaf). These results indicate that the annual cyclic reconfiguration of FMD gut microbiota could be associated with shifts in dietary nutrients, which is important information to inform captive FMD management.